Three-band Anderson-Mott-Hubbard model for the metal-insulator transition in cubic disordered tungsten bronzes NaxWO3 and NaxTayW1-gamma O3 - Ducker, H; von Niessen, W; Koslowski, T; Tusch, M; Logan, D (1999)
A microscopic three-band Anderson-Mott-Hubbard model for cubic disordered tungsten bronzes NaxWO3 and NaxTayW1-yO3 is studied over a range of doping levels x-y at the level of an unrestricted Hartree-Fock approximation in order to understand the effects of disorder and electron interaction on the electronic ground state and their implications for the chemically induced metal-insulator transition observed at least in the latter materials. For sufficiently large U a pseudogap develops at EF in agreement with photoemission spectra and tunneling current measurements which is found to significantly affect the localization and hybridization characteristics as well as the three-dimensional spatial distribution of quasiparticle states and thus constitutes the central feature of the model. The formation of the pseudogap is rationalized via a repulsion between occupied and unoccupied conduction band quasiparticle states induced by antiferromagnetic correlations occurring on length scales which - for the most relevant parameters - are controlled by the doping-dependent tight-binding Fermi surface. Light is shed on experimental results which hitherto have not found a satisfactory rationalization. © 1999 The American Physical Society.